THE ROLE OF OUR GREAT ANCESTORS IN SCIENCE AND CULTURE - Salohiddinov Bunyod (Ustozlar uchun, 2023)
Abstract: In this article, the great geniuses of the East who lived and created in the 9th-12th centuries, Muhammad ibn Musa al-Khorazmi, al-Farghani, Abu Nasr Farabi, Abu Ali ibn Sina, Abu Rayhan Beruni, and the great representatives of the Islamic world, Imam Bukhari, at-Tirmidhi , Abu Mansur al-Moturidi, Burhoniddin al-Marginani, the life path and activities of scientists are widely covered, and their contribution to world science and culture is analyzed on the basis of sources.